Acceleration optimization of real-time equilibrium reconstruction for HL-2A tokamak discharge control - 马瑞;夏凡;凌飞;李佳鲜 (Plasma science & technology, 2018)
Real-time equilibrium reconstruction is crucially important for plasma shape control in the process of tokamak plasma discharge.However,as the reconstruction algorithm is computationally intensive,it is very difficult to improve its accuracy and reduce the computation time,and some optimizations need to be done.This article describes the three most important aspects of this optimization：（1） compiler optimization;（2） some optimization for middle-scale matrix multiplication on the graphic processing unit and an algorithm which can solve the block tri-diagonal linear system efficiently in parallel;（3） a new algorithm to locate the X＆O point on the central processing unit.A static test proves the correctness and a dynamic test proves the feasibility of using the new code for real-time reconstruction with 129？×？129 grids;it can complete one iteration around 575 μs for each equilibrium reconstruction.The plasma displacements from real-time equilibrium reconstruction are compared with the experimental measurements,and the calculated results are consistent with the measured ones,which can be used as a reference for the real-time control of HL-2 A discharge.